1999
DOI: 10.1039/a902091h
|View full text |Cite
|
Sign up to set email alerts
|

Peptide nucleic acids (PNA) derived from N-(N-methylaminoethyl)glycine. Synthesis, hybridization and structural properties

Abstract: Backbone N-methylated peptide nucleic acids (PNAs) containing the four nucleobases adenine, cytosine, guanine and thymine were synthesized via solid phase peptide oligomerization. The oligomers bind to their complementary target with a thermal stability that is 1.5È4.5 ¡C lower per "" N-methyl nucleobase unit ÏÏ [dependent on the number and position(s) of the N-methyl] than that of unmodiÐed PNA. However, even fully N-methyl modiÐed PNAs bind as efficiently to DNA or RNA targets as DNA itself. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 19 publications
4
41
0
Order By: Relevance
“…The crystal structure of the (PNA) 2 -DNA triplex (10) also showed helical parameters significantly different from those of canonical DNA or RNA helical forms, defining a type of helix, named the P-helix, characterized by a small twist angle, a large x-displacement, and a wide, deep major groove. Finally, structural features of the PNA-PNA double helix (11)(12)(13) are similar to those of the P-helix mentioned above.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…The crystal structure of the (PNA) 2 -DNA triplex (10) also showed helical parameters significantly different from those of canonical DNA or RNA helical forms, defining a type of helix, named the P-helix, characterized by a small twist angle, a large x-displacement, and a wide, deep major groove. Finally, structural features of the PNA-PNA double helix (11)(12)(13) are similar to those of the P-helix mentioned above.…”
supporting
confidence: 52%
“…Water molecules located in the minor groove are also stabilized by H-bonds with nucleobases (purine-N3 or pyrimidine O2). In particular, those bound to the PNA strand form a bridge between the nucleobases and the amides of the backbone (N or O depending on the orientation of the amide bond), as observed for the PNA-PNA structure (11)(12)(13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary amides in an aegPNA backbone have been modified to a tertiary N-methyl amide, although moderate loss in binding to DNA is observed (94, Fig. 27) [130]. The work of Efimov et al elegantly showed that the secondary amides of a e g PNA can be replaced with a phosphonate or phosphonamide, again with moderate reduction in binding to DNA (95, Fig.…”
Section: Fluorinated Pnasmentioning
confidence: 96%
“…Furthermore, two enlightening studies on PNAs showing N γ alkylation, [19] indicated that the N-H H-bonding was not crucial for the stabilization of the PNA/nucleic acid double strand. Thus, we reasoned that N-alkylation of the backbone with polar groups, in a pure peptoid framework, could represent a novel strategy for a fine-tuning of PNA properties and provide a new way to overcome the pressing water-solubility issue.…”
Section: Introductionmentioning
confidence: 98%